Participation of Beginner Voters in Political Education in the 2024 Election in Palembang City (Case Study of the Kesbangpol Agency of Palembang City) - Erlina, Erlina; Kariem, M. Qur’anul; Amaliatulwalidain, Amaliatulwalidain (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The purpose of this study is to determine the political education of novice voters in the 2024 Election in Palembang City (Case Study of the National and Political Unity Agency of Palembang City). The type of research used in this study is descriptive qualitative method. Data collection techniques use primary data in the form of observations and interviews. Data analysis using Miles and Huberman (data reduction, data presentation, and inference). The results of the study discuss the participation of novice voters in political education in the 2024 election in Palembang City by the National and Political Unity Agency of Palembang City. The situation on the eve of the election until now has not been uproar. Public participation to participate in local election activities, these factors are influenced by a better understanding and attention to politics that tends to contribute to the community environment to participate in regional elections, one's organizational experience in political participation activities applies to political and pseudo-political organizations. A parent's political affiliation can influence a person's participation in exercising their voting rights in local elections. With the problems that occur in Palembang City, voter participants, especially novice voters, can vote. The evaluation conducted by the Kesbangpol Agency refers to the results of participation increased by 11.74% from 70.26% in the 2018 regional elections to 82% (214,446 voters). Kesbangpol has done a good job to increase the political participation of beginners by visiting schools and as a result in the 2019 elections the increase exceeded the national target of 77.5%